Exploratory Factor Analysis of Reading, Spelling, and Math Errors. (February 2017) - O'Brien, Rebecca; Pan, Xingyu; Courville, Troy; Bray, Melissa A.; Breaux, Kristina; Avitia, Maria; Choi, Dowon
Norm-referenced error analysis is useful for understanding individual differences in students' academic skill development and for identifying areas of skill strength and weakness. The purpose of the present study was to identify underlying connections between error categories across five language and math subtests of the Kaufman Test of Educational Achievement–Third Edition (KTEA-3) through exploratory factor analyses (EFAs). The EFA results were supportive of models with two or three factors for each of the five subtests. Significant inter-factor correlations within subtests were identified in all subtests, except between two factors within the Math Concepts and Application (MCA) subtest. There was also consistency in the covariance patterns of some error categories across subtests, particularly within the Nonsense Word Decoding (NWD) and Spelling (SP) subtests. This consistency was supportive of the proposed factor structures. The factor structures yielded by these analyses were used as the bases for the other articles in this special issue.